Effective visual representation: graphic style and the communication of design intent - Prudenti, Richard (Kansas State University, 2018)
Landscape architecture lacks evidence-based theory for the communicative effectiveness of graphics used in representing design ideas to stakeholders. For the purpose of this study, communicative effectiveness is operationalized as visual communication that expresses accurately the design in a way that the receiver understands the intentions — programmatic, experiential or otherwise — of the design. People need graphic representation to grasp abstract concepts, and drawings can help one imagine what a place can look like years down the road (Hester 2007). Graphics inform the viewer about essential elements of the design and the broader impact that design has on future experiences (Coe 1981). Knowing how people perceive and understand design graphics is key to communicating effectively to clients and other stakeholders. Graphic communication is complex, and no formula exists for communication in landscape architecture (Kingery-Page and Hahn 2012; Ware 2014). The questions guiding this study are: What graphic representation styles increase the non-designers’ understanding of design proposals? Do degrees of abstraction or realism affect understanding of the design drawing? I identified three research phases to adequately answer the questions: Phase One: Site Design Development — I designed a site plan for the Manhattan Arts Center (MAC), a community arts center in Manhattan, Kansas. Design intentions were carefully outlined based on stakeholder input. Phase Two: Graphics Production — Visual representations of the site design were developed in styles ranging from formal abstract to more realistic, based on review of precedent images in academic and professional architectural publications. Phase Three: Evaluation of Graphics Through Focus Groups— The communicative effectiveness of the representations were tested through three focus groups of stakeholders. Content analysis of the recorded focus group sessions revealed patterns of understanding the graphics. Overall, participants revealed that the more real the abstraction, the less understanding takes place. Formal Abstraction communicates the physical dimensions of the design most effectively, and Formal Abstraction has relatively the same communicative effectiveness regarding experience of place. Quantitative and qualitative data informed the creation of theories and a framework practitioners may use for selecting the most effective graphic communication options appropriate to project and audience. Key Words: Effective visual representation, visual communication, graphic style, Formal Abstraction, Semi-Realistic Abstraction, Realistic Abstraction, drawings, design intent, design ideas, accurate, perception, understanding, stakeholders, non-designer, landscape architecture.
Keywords: Visual representation; Visual communication; Graphic style; Abstraction; Realistic; Design ideas